Strategies For Developing Tourism And Creative Economy Based On Local Wisdom In Supporting Sustainable Development In Kuningan Regency - Aep Saefullah; Sukardi Sukardi; Rianti Salima (LPPM Universitas PGRI Sumatera Barat, 2025)
Tourism and the creative economy are strategic sectors that significantly contribute to sustainable development, functioning not only as drivers of economic growth but also as instruments of cultural preservation and environmental protection. Kuningan Regency, West Java, holds considerable potential to develop these sectors due to its natural landscapes, cultural diversity, and preserved local wisdom. Data from the Youth, Sports, and Tourism Office recorded 3,278,975 tourist visits in 2024, reflecting both strong attractiveness and promising opportunities for strengthening the local creative economy. However, tourism development often faces challenges such as limited funding, lack of creativity, and suboptimal community participation. This study aims to formulate sustainable strategies for tourism and creative economy development based on local wisdom in Kuningan Regency. A descriptive qualitative method with data triangulation was employed. Data collection involved in-depth interviews, focus group discussions (FGDs), field observations, and official documents, engaging local government, creative economy actors, community leaders, and residents. Data analysis was conducted through thematic coding using NVivo software, with categories including supporting factors, challenges, collaboration patterns, and relevant values of local wisdom. The findings reveal four critical factors for successful sustainable tourism in Kuningan: (1) integrating local wisdom into tourism and creative economy products; (2) multi-stakeholder collaboration between government, private sector, and community; (3) the use of digital technology for destination marketing and management; and (4) community-based environmental conservation strategies. The novelty of this study lies in its comprehensive framework that integrates cultural, economic, technological, and ecological dimensions in the context of sustainable tourism development. The study concludes that a holistic strategy emphasizing implementation evaluation, stakeholder engagement, and technology-driven innovation is essential to enhance Kuningan’s tourism competitiveness while safeguarding socio-cultural and environmental sustainability. These findings are expected to provide both academic insights and practical recommendations for other regions with similar characteristics